Challenging the Neoliberal Consensus: Islamic Populism as an Alternative Development Narrative in Post-Pandemic Malaysia - Honest Dody Molasy; Erwin Nur Rif’ah; Sus Eko Zuhri Ernada (Jurnal Impresi Indonesia, 2026)
This research examines the unprecedented electoral realignment in Malaysia’s 15th General Election (GE-15), widely referred to as the "Green Wave," which led to the dramatic rise of the Islamic populist coalition, Perikatan Nasional (PN). Moving beyond reductionist narratives of spontaneous theological revival, this study argues that the Green Wave represents a profound grassroots protest against the structural inequities of neoliberal development. The research employed a qualitative approach using a case study design, combining Critical Discourse Analysis (CDA) of political speeches, manifestos, and elite narratives with the analysis of secondary socio-economic data, including post-pandemic inequality indicators and electoral results. The research traces the collapse of Malaysia's traditional Islamic Leviathan, the UMNO-led political establishment, which lost its moral and institutional legitimacy due to the 1MDB kleptocracy scandal and its failure to protect vulnerable demographics during the post-pandemic economic crisis. This state failure generated a severe "development deficit," fracturing the historical social contract. In this vacuum, PN and its ideological anchor, Parti Islam Se-Malaysia (PAS), successfully mobilized subaltern class grievances by articulating an alternative, morally charged developmental rhetoric that demanded "Clean and Stable" governance. Furthermore, PAS consolidated its political capital by operating a faith-based "shadow state" at the local level, providing vital alternative welfare and social services where the formal state had retreated. Ultimately, this article posits that the Malaysian phenomenon holds crucial implications for the Global South, demonstrating that Islamic identity politics now serves as a primary and sophisticated channel for marginalized populations to articulate anti-neoliberal critiques and demand distributive justice.